Pengaruh Pendidikan Kesehatan dengan Media Booklet Anti ISPA (BOOKIS) terhadap Perilaku Pencegahan ISPA pada Ibu Balita - Ni Putu Diah Ameliya Putri; I Ketut Gama (Jurnal Gema Keperawatan, 2020)
Upper Respiratory Tract Infections (URTI) is an acute infection involving the organ of the upper respiratory tract and the bottom of which can cause a range of illnesses from mild infection to weight and turn off. The purpose of this research was to determine the effect of health education with anti-URTI Booklet media on URTI prevention behavior in mothers of children under five years old. This research was conducted in April-May 2019. This type of research is a quasy experiment with a pre-test and post-test design. This research used 61 people as a sample with used the total sampling technique. The results of this study indicate that from 61 respondents before given treatment had goof behavioral categories as much as 57.4% and after being treated 96.7% had good value categories. Hypothesis testing using the Wilcoxon test results in a p value of 0,000 (p value 0.05) which means that there is an effect of health education with the Anti-URTI Booklet media on URTI prevention behavior in mothers of children under five years old. Based on the results of the study it is suggested that it can improve efforts to prevent URTI in infants using the Anti-URTI Booklet (BOOKIS).